Adapting to the New Legal Landscape: Opportunities and Challenges in Legal Technology Integration - Ramos Zaga , Fernando Antonio (2024)
In recent times, the rapid advancement of technology has sparked discussions regarding its profound impact on various aspects of both personal and professional life. This article seeks to examine the opportunities and challenges posed by Legal Technologies, focusing on how legal professionals can adapt to the evolving legal landscape through the acquisition of new skills. To achieve this objective, a literature review was conducted, employing specific inclusion and exclusion criteria to identify relevant studies. The study's findings underscore the pivotal role of Legal Technology in enhancing legal practice by streamlining workflows and automating tasks. Consequently, the swift technological progress within the legal sector offers prospects that necessitate a reevaluation of curricular content to equip future legal practitioners with the requisite knowledge and competencies for the effective utilization of these emerging technologies.